2019
DOI: 10.4102/sajip.v45i0.1768
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing scientific credibility: An open science strategy for the South African Journal of Industrial Psychology

Abstract: Orientation: The purpose of this editorial was to provide an introduction and a general overview of the special issue on Open Science Practices: A Vision for the Future of SAJIP, as hosted in the 45th edition of the South African Journal of Industrial Psychology (SAJIP). Specifically, the aim was to provide a viable, practical and implementable strategy for enhancing the scientific credibility, transparency and international stature of SAJIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The growth of the discipline resulted in a rapid rise in the development and use of "positive psychological assessment measures" (PPAMs) aimed at measuring these positive psychological constructs validly and reliably (4). However, critics of positive psychology have questioned the validity of PPAMs (5)(6)(7)(8). Psychometric evaluations of PPAMs have shown that various instruments produce inconsistent factor structures, that reliability estimates vary significantly between groups/contexts/times frames, that the predictive validity is questionable and that popular PPAMs are culturally biased [cf.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the discipline resulted in a rapid rise in the development and use of "positive psychological assessment measures" (PPAMs) aimed at measuring these positive psychological constructs validly and reliably (4). However, critics of positive psychology have questioned the validity of PPAMs (5)(6)(7)(8). Psychometric evaluations of PPAMs have shown that various instruments produce inconsistent factor structures, that reliability estimates vary significantly between groups/contexts/times frames, that the predictive validity is questionable and that popular PPAMs are culturally biased [cf.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its growth and impact, positive psychology encounters challenges. Since its formal inception in 2000, numerous scholars have raised questions regarding the distinctive contribution of the paradigm and the validity of its theories, methods, interventions, and philosophical foundations (Brown et al, 2014;Goodman et al, 2017;Compton and Hoffman, 2019;Van Zyl, 2019;Yakushko, 2019). Wong and Roy, (2017)has also made similar criticism.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its growth and contribution, positive psychology is not without its challenges. Since its formal inception in 2000, many scholars have questioned the unique contribution of the paradigm as well as the validity of the theories, methods, interventions, and philosophy underpinning the discipline (Brown et al, 2014 ; Goodman et al, 2017 ; Wong and Roy, 2017 ; Compton and Hoffman, 2019 ; Van Zyl, 2019 ; Yakushko, 2019 ). This, in turn, has negatively affected positive psychology's scientific credibility and public perception (Van Zyl and Ten Klooster, 2022 ).…”
Section: Introductionmentioning
confidence: 99%